POC08 A case of central and peripheral vestibular vestibular failure. Issue 11 (22nd October 2010) - Doherty, K M C; Ling, H; Mulroy, E; Foung-Tai, Y; Djamshidian, A; Silveria-Moriyama, L; Massey, L; Brew, S; Lees, A J
Abstract : A 63-year old male presented with a 3-year history of worsening mobility due to difficulty maintaining balance and deterioration in his hearing. He had a past medical history of ankylosing spondylitis treated with radiotherapy and NSAIDs. Cranial nerve examination revealed anosmia, bidirectional gaze-evoked nystagmus and jerky pursuit eye movements. Hearing and taste were impaired and his speech was slurred. He had gross truncal ataxia, an unsteady wide-based gait and bilateral Babinski reflexes. Otological testing revealed sensorineural deafness and absent acoustic brain stem evoked responses. Vestibular assessment confirmed bilateral vestibular failure (positive Halmagyi head thrust test and absent caloric responses). T2-weighted MRI was diagnostic; it illustrated low signal along the surface of the cerebellar folia, the brainstem, throughout the Sylvian fissure, the midline sagittal sulcus and along the length of the spinal cord. This was in keeping with haemosiderin deposition and a diagnosis of superficial siderosis. Despite full cerebral and spinal angiography and venography no source of bleeding was found. The patient was started on Trientine chelation therapy. Superficial siderosis has never previously been reported in conjunction with ankylosing spondylitis (AS). The possible underlying mechanism may be AS-associated dural ectasia with inflamed meningitic vessels prone to chronic venous bleeding (Abstract POC08 Figure 1 ).